2008
DOI: 10.4103/0974-1208.39594
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin releasing hormone antagonist in IVF/ICSI

Abstract: OBJECTIVE:To study the efficacy of gonadotrophin releasing hormone (GnRH) antagonist in In-vitro-fertilization/Intracytoplasmic sperm injection (IVF/ICSI) cycles.TYPE OF STUDY:Observational study.SETTING:Reproductive Medicine Unit, Christian Medical College Hospital, Vellore, Tamil Nadu.MATERIALS AND METHODS:GnRH antagonists were introduced into our practice in November 2005. Fifty-two women undergoing the antagonist protocol were studied and information gathered regarding patient profile, treatment parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The literature regarding the cost effectiveness of GnRH antagonist protocols is currently contradictory. In a randomized trial by Badrawi et al [15], the cost of medication per cycle and per pregnancy was shown to be higher in a GnRH antagonist protocol than a GnRH agonist protocol, while an observational study by Kamath et al [16] found costs of the two protocols to be similar.…”
Section: Introductionmentioning
confidence: 99%
“…The literature regarding the cost effectiveness of GnRH antagonist protocols is currently contradictory. In a randomized trial by Badrawi et al [15], the cost of medication per cycle and per pregnancy was shown to be higher in a GnRH antagonist protocol than a GnRH agonist protocol, while an observational study by Kamath et al [16] found costs of the two protocols to be similar.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of ‘confirmed OHSS’ requiring ICU admission per fresh IVF cycle has halved over recent years, from 0.06% in 1996-2006 to 0.03% in 2007-2019. This decline is likely to reflect the introduction of safer IVF practices including individualized dosing of gonadotropins for ovarian stimulation, using predictive markers such as AMH ( 15 , 21 ), and increased use of GnRH antagonist co-treated protocols ( 12 , 17 ). Furthermore, the reduced use of fresh embryo transfer cycles ( 13 , 14 ) from 82% in 2008 to 77% in 2019 ( 19 ), and the increased use of frozen embryo transfer (FET) may also have contributed to a reduction in OHSS requiring ICU admission ( 13 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… Demographic data of female patients aged between 18-55 years presenting to an ICU in England, Wales or Northern Ireland. Data is collected from the ICNARC database ( 17 ) presented between the years 1996 to September 30 th , 2020. Data are presented as median (25 th quartile, 75 th quartile).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations